Thermally conductive silicone composition and method for producing thermally conductive member using same
By using the predetermined heating fillers with a scheduled ratio and particle size in the heating silicone composition, and adding a silicol -containing silicoxane with a specific viscosity to solve the problem of insufficient storage and heat resistance of thermal conductivity. Realize efficient thermal conductivity and flexibility.
Patent Information
- Application Number
- CN202380046586.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-15
- Filing Date
- 2023-06-13
- Publication Date
- 2025-01-24
AI Technical Summary
The existing thermally conductive silicone compositions have shortcomings in storage stability and heat resistance, resulting in a change in mass of the thermally conductive member and a decrease in thermal conductivity.
Use a thermally conductive filler containing a predetermined BET specific surface area and average particle size, and add a silanol group-containing organopolysiloxane with a viscosity of 10mPa·s to 500mPa·s at 25°C to improve the storage of the thermally conductive silicone composition Stability and flexibility.
It achieves high storage stability and flexibility of the thermally conductive component, ensures quality stability over a long period of time, and improves the thermal conductivity of the thermally conductive component.
Smart Images

Figure BDA0005184063740000411 
Figure BDA0005184063740000421 
Figure BDA0005184063740000431
Abstract
Description
Technical Field
[0001] The present invention relates to a curable thermally conductive silicone composition containing a thermally conductive filler and a dimethyl polysiloxane containing a predetermined silanol group, and a method for producing a thermally conductive member using the composition. Prior art
[0002] As electronic components become smaller, more efficient, and have higher output, the heat energy generated increases, and the temperature of the electronic components tends to rise. In recent years, with the popularization of environmentally friendly electric vehicles, high-performance batteries have been developed. In view of this background, various heat dissipation silicone products (heat sinks, heat dissipation greases, heat dissipation gap fillers, etc.) have been developed to transfer heat generated by a heat generating body (e.g., electronic components and batteries) to a heat dissipation member (e.g., a radiator).
[0003] Heat sinks have excellent shape retention after curing and have excellent handleability. However, compared to grease and gap fillers, heat sinks are more difficult to make into films and have poor flexibility after curing, and therefore the contact thermal resistance between the heat sink and the heat dissipation component tends to increase. Heat dissipation grease has excellent flexibility and tends to achieve low thermal resistance, but has problems in resisting pump-out due to uncuring. From this point of view, further improvements in performance are expected, and gap fillers, which are a material with high flexibility before curing, curing properties, pump-out resistance and low thermal resistance, are of particular interest.
[0004] A gap filler as a mode of a thermally conductive member is obtained by curing a curable thermally conductive silicone composition. When a thermally conductive filler is mixed in the composition, high heat dissipation performance can be imparted to the gap filler obtained by curing. Specifically, a large amount of thermally conductive fillers (e.g., spherical thermally conductive fillers) having a relatively small specific surface area can be mixed in a polymer. For example, a thermally conductive filler is an important component for obtaining a thermally conductive member having a high thermal conductivity of 2.0 W / m·K or more. However, the spherical thermally conductive filler is likely to precipitate in the thermally conductive silicone composition, and therefore has problems in long-term storage stability.
[0005] In addition to favorable heat dissipation performance, when an impact is applied to a vehicle body, a heat conduction member is also expected to reduce the impact applied to electronic parts, batteries, heat dissipation members, etc. Therefore, a heat conduction member having high flexibility is required.
[0006] It is believed that in order to obtain a thermally conductive member having high flexibility, a low-viscosity polymer should be mixed in the thermally conductive silicone composition. However, there is a problem that the thermally conductive filler in the thermally conductive silicone composition is likely to precipitate over time. When the thermally conductive filler precipitates, the chemical composition of the thermally conductive silicone composition becomes uneven, and thus the quality of the obtained thermally conductive member may also vary. Therefore, various methods of preventing the precipitation of thermally conductive fillers have been developed.
[0007] For example, PTL 1 discloses a thermally conductive silicone composition in which a thermally conductive filler containing 70% by mass or more of aluminum hydroxide is mixed to suppress precipitation of the thermally conductive filler. However, the resulting cured product has insufficient flexibility.
[0008] PTL 2 discloses a silicone composition containing liquid silicone, a filler material imparting an insolubility function (e.g., a thermally conductive filler material or an electrically conductive filler material), and a material that inhibits thickening and prevents precipitation (e.g., a non-liquid cellulose-based compound, or a polysaccharide or a non-thickening and anti-precipitation material). However, during exposure to high temperatures, polysaccharides undergo thermal decomposition, and thus flexibility and thermal conductivity may decrease. Therefore, there is a problem of low heat resistance to thermal decomposition during exposure to high temperatures. Reference List Patent Literature
[0009] PTL 1: Japanese Patent Application Publication No. 2011-089079 PTL 2: WO2016 / 103424 Summary of the invention Technical issues
[0010] Under such circumstances, an object of the present invention is to provide a thermally conductive silicone composition for obtaining a thermally conductive member having high flexibility and excellent heat dissipation performance, the thermally conductive silicone composition having excellent storage stability and heat resistance. Solutions to the problem
[0011] The present inventors have found that the problems of the present invention can be solved when a silicone composition containing an organopolysiloxane contains a thermally conductive filler having a predetermined BET specific surface area and a predetermined average particle size and also contains a silanol group-containing organopolysiloxane having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C. The present invention has thus been completed.
[0012] The thermally conductive silicone composition according to the present invention is a thermally conductive silicone composition containing the following components: Component (A) which is an alkenyl group-containing organopolysiloxane; Component (B) which is an organopolysiloxane having two or more hydrosilyl groups in one molecule; Component (C) which is a silanol group-containing organopolysiloxane having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C.; a component (D) which is an addition reaction catalyst; Component (E), which is one or more types of thermally conductive fillers selected from the following group: metals, metal oxides, metal hydroxides, metal nitrides, and metal carbides, the thermally conductive filler having 30m 2 / g or less, and an average particle size of 1 μm to 100 μm; and Component (F), which is a crosslinking agent, wherein Based on 100 parts by weight of the total amount of component (A) and component (B), the BET specific surface area of the composition is 50 m 2 / g or more of the filler is 3 parts by mass or less.
[0013] The thermally conductive silicone composition (hereinafter referred to as the composition) of the present invention is a composition for forming a thermally conductive member provided on the surface of a substrate as a heat generating body, etc. Examples of the form of the thermally conductive member include a gap filler.
[0014] In the presence of an addition reaction catalyst (D), the alkenyl group-containing organopolysiloxane (A) and the organopolysiloxane (B) having two or more hydrosilyl groups in one molecule in the thermally conductive silicone composition undergo a crosslinking reaction, thereby curing. The silanol group-containing organopolysiloxane (C) having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C. has neither a hydrosilyl group nor an alkenyl group, and therefore does not contribute to the crosslinking reaction. This can improve the flexibility of the cured product.
[0015] Furthermore, the present inventors have found that when component (C) is mixed, the effect of suppressing the precipitation of the thermally conductive filler in the composition is higher than when an organopolysiloxane having no silanol group is mixed. Such higher suppression is believed to be due to the fact that the compatibility of component (A) with component (B) is favorable because the OH groups on the surface of the thermally conductive filler form hydrogen bonds with the silanol groups of component (C), and also because component (C) has an organopolysiloxane skeleton.
[0016] In particular, when mixed with a silanol group-containing organopolysiloxane having a viscosity of 500 mPa·s or less at 25°C, the composition obtained thereby can exhibit a sufficiently high effect of improving the flexibility of the cured product and a sufficiently high effect of inhibiting the precipitation of the thermally conductive filler. More specifically, a thermally conductive silicone composition is obtained, which forms a gap filler having a needle penetration of 10 or more according to JIS K6249 and extremely high flexibility, and has high storage stability, wherein after storage at room temperature for 1000 hours, the specific gravity difference between the upper and lower parts of the composition is 0.2 or less. An organopolysiloxane having a low viscosity of 500 mPa·s or less has a low degree of polymerization, and thus the density of the above-mentioned hydrogen bonds increases. Therefore, it is believed that such an organopolysiloxane exhibits a higher effect than an organopolysiloxane having a high viscosity containing a silanol group. Advantageous Effects of the Invention
[0017] As described above, the thermally conductive silicone composition according to the present invention has high storage stability, and the thermally conductive component obtained by curing the thermally conductive silicone composition has excellent flexibility. Therefore, the obtained thermally conductive component has stable quality over a long period of time. When the thermally conductive component is used as a gap filler for a heat dissipation component applied to a component (e.g., a battery) to be installed in a car body, the external mechanical impact on the heat dissipation component can be reduced. DETAILED DESCRIPTION
[0018] Hereinafter, a thermally conductive silicone composition according to the present invention, a method of producing the composition, and a method of producing a thermally conductive member using the composition will be explained in detail.
[0019] The thermally conductive silicone composition according to the present invention is a thermally conductive silicone composition containing the following components: Component (A) which is an alkenyl group-containing organopolysiloxane; Component (B) which is an organopolysiloxane having two or more hydrosilyl groups in one molecule; Component (C) which is a silanol group-containing organopolysiloxane having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C.; a component (D) which is an addition reaction catalyst; Component (E), which is one or more types of thermally conductive fillers selected from the following group: metals, metal oxides, metal hydroxides, metal nitrides, and metal carbides, the thermally conductive filler having 30m 2 / g or less, and an average particle size of 1 μm to 100 μm; and Component (F), which is a crosslinking agent, wherein Based on 100 parts by weight of the total amount of component (A) and component (B), the BET specific surface area of the composition is 50 m 2 / g or more of the filler is 3 parts by mass or less.
[0020] When a silanol group-containing organopolysiloxane having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C. as component (C) is added to a composition containing the above components (A), (B), (D) and (E), the flexibility of a thermally conductive member obtained by curing the composition can be improved. In addition, precipitation of the thermally conductive filler during storage of the composition can be suppressed, so that the storage stability of the composition can be improved.
[0021] The thermally conductive silicone composition of the present invention may be any composition as long as the composition can be formed into a thermally conductive member, and examples of the thermally conductive member include gap fillers applied to a heat generating body (eg, a battery of a vehicle) and applied to a film covering such a heat generating body. The thermally conductive silicone composition of the present invention, which is in a liquid state before curing, is applied to a substrate and cured to obtain a thermally conductive member.
[0022] Component (A): Component (A), which is a main component of the thermally conductive silicone composition, is an organopolysiloxane having an alkenyl group bonded to a silicon atom. The viscosity and degree of polymerization of component (A) are not particularly limited and may be selected according to the desired mixed viscosity of the thermally conductive silicone composition, etc., and the viscosity may be, for example, 10 mPa·s or more and 10,000 mPa·s or less at 25°C. As the organopolysiloxane, one type thereof may be used alone, or two or more types thereof may be used in combination as appropriate. The organopolysiloxane is a main component of the thermally conductive silicone composition and has an average of at least 2 alkenyl groups bonded to silicon atoms in one molecule, preferably 2 to 50 alkenyl groups, and more preferably 2 to 20 alkenyl groups.
[0023] Component (A) has no specific molecular structure, and may have, for example, a linear structure, a partially branched linear structure, a branched structure, a cyclic structure, or a branched cyclic structure. Among them, component (A) is preferably a substantially linear organopolysiloxane, and specifically, component (A) may be a linear diorganopolysiloxane in which the molecular chain is mainly composed of diorganosiloxane repeating units, and both ends of the molecular chain are capped with triorganosiloxy groups. Some or all of the molecular chain ends or some side chains may be silanol groups.
[0024] The position of the alkenyl group bonded to the silicon atom in component (A) is not particularly limited, and component (A) may be an organopolysiloxane having alkenyl groups bonded to the silicon atom at both molecular chain ends. The advantages of a diorganopolysiloxane having one alkenyl group at each molecular chain end are that the alkenyl content serving as a reaction point for a crosslinking reaction is small and the flexibility of the gap filler obtained after curing is enhanced.
[0025] The alkenyl group may be bonded to a silicon atom located at a molecular chain terminal, to a silicon atom located at a non-terminal molecular chain site (in the middle of the molecular chain), or to both. Component (A) may be a polymer composed of a single type of siloxane unit, or a copolymer composed of two or more types of siloxane units.
[0026] The viscosity of component (A) at 25° C. is 10 mPa·s or more and 10,000 mPa·s or less, preferably 20 mPa·s or more and 5,000 mPa·s or less, and more preferably 30 mPa·s or more and 2,000 mPa·s or less. When the viscosity falls within the above-mentioned viscosity range, since component (A) has an extremely low viscosity, the phenomenon that component (E) may precipitate in the obtained liquid composition can be suppressed. Therefore, a thermally conductive silicone composition having excellent long-term storage stability can be obtained. In addition, when the viscosity of component (A) falls within the above-mentioned viscosity range, the obtained thermally conductive silicone composition can have appropriate fluidity, and thus the dischargeability can be improved and the productivity can be improved. In addition, the flexibility of the thermally conductive member obtained by curing the thermally conductive silicone composition can be improved.
[0027] In order to adjust the viscosity (mixed viscosity) of the thermally conductive silicone composition obtained by mixing the liquid compositions before curing, two or more types of organopolysiloxanes having alkenyl groups and having different viscosities may be used in combination. In order to ensure appropriate fluidity of the thermally conductive silicone composition and flexibility of a thermally conductive member obtained by curing the composition, component (A) preferably does not contain a diorganopolysiloxane having a viscosity of 100,000 mPa·s or more at 25°C, and more preferably does not contain 0.1 parts by mass or more of a diorganopolysiloxane having a viscosity of 50,000 mPa·s or more at 25°C, based on 100 parts by mass of the total amount of component (A) and component (B).
[0028] Specifically, component (A) is represented by the following general formula (1) as an average composition formula: R 1 a SiO (4-a) / 2 (1) In formula (1), R1 are the same as or different from each other and are each an unsubstituted or substituted monovalent hydrocarbon group having 1 to 18 carbon atoms, and a is 1.7 to 2.1, preferably 1.8 to 2.5, and more preferably 1.95 to 2.05.
[0029] In one embodiment, the above R 1 Two or more of the monovalent hydrocarbon groups represented by are selected from alkenyl groups, such as vinyl, allyl, propenyl, isopropenyl, butenyl, isobutenyl, hexenyl and cyclohexenyl. Groups other than these groups are substituted or unsubstituted monovalent hydrocarbon groups having 1 to 18 carbon atoms. Specifically, the above R 1 is selected from the following groups: alkyl groups, such as methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, 2-ethylhexyl, heptyl, octyl, nonyl, decyl and dodecyl; cycloalkyl groups, such as cyclopentyl, cyclohexyl and cycloheptyl; aryl groups, such as phenyl, tolyl, xylyl, biphenyl and naphthyl; aralkyl groups, such as benzyl, phenethyl, phenylpropyl and methylbenzyl; and alkyl groups substituted with halogen or cyano, wherein some or all of the hydrogen atoms in the above hydrocarbon groups have been substituted with halogen atoms, cyano, etc., such as chloromethyl, 2-bromoethyl, 3,3,3-trifluoropropyl, 3-chloropropyl and cyanoethyl.
[0030] R to be selected 1 The following groups are preferably contained as the required two or more alkenyl groups: vinyl, allyl, propenyl, isopropenyl, 2-methyl-1-propenyl, 2-methylallyl or 2-butenyl, and vinyl is particularly preferred. 1 Preferably, methyl or phenyl is present, and methyl is particularly preferred. In addition, in consideration of the physical properties and economic efficiency of the cured product, preferably 70 mol % or more of R 1 is methyl, and usually, preferably 80 mol% or more of R 1 It is methyl.
[0031] Specific examples of the molecular structure of component (A) include dimethylpolysiloxane in which both molecular chain ends are capped with dimethylvinylsiloxy groups, dimethylsiloxane-methylphenylsiloxane copolymer in which both molecular chain ends are capped with dimethylvinylsiloxy groups, dimethylsiloxane-methylvinylsiloxane copolymer in which both molecular chain ends are capped with dimethylvinylsiloxy groups, dimethylsiloxane-methylvinylsiloxane-methylphenylsiloxane copolymer in which both molecular chain ends are capped with dimethylvinylsiloxy groups, and dimethylsiloxane-methylvinylsiloxane copolymer in which both molecular chain ends are capped with trimethylsiloxy groups; 3 ) 2 ViSiO1 / 2 The siloxane unit represented by the formula (CH 3 ) 3 SiO 1 / 2 The siloxane unit represented by the formula SiO 4 / 2 Organopolysiloxanes composed of siloxane units represented by (wherein Vi represents a vinyl group); organopolysiloxanes in which part or all of the methyl groups in the above organopolysiloxanes are substituted with alkyl groups (e.g., ethyl or propyl), aryl groups (e.g., phenyl or tolyl) and halogenated alkyl groups (e.g., 3,3,3-trifluoropropyl); and mixtures of two or more of these organopolysiloxanes. From the viewpoint of increasing the elongation of the cured product at break due to an increase in the molecular chain length, linear diorganopolysiloxanes having vinyl groups at both molecular chain ends are preferred.
[0032] These organopolysiloxanes are commercially available or can be prepared by methods known to those skilled in the art.
[0033] The content of the organopolysiloxane as component (A) is preferably 2 parts by mass or more and less than 90 parts by mass, and more preferably 10 parts by mass or more and 80 parts by mass or less, based on 100 parts by mass of the total amount of component (A) and component (B) in the thermally conductive silicone composition of the present invention. When the content falls within the above range, the viscosity of the entire thermally conductive silicone composition is within an appropriate range, and the thermally conductive silicone composition has excellent and longer long-term storage stability, exhibits appropriate fluidity, and can suppress pumping out. Therefore, the high thermal conductivity of the obtained thermally conductive member can be maintained. In this article, the pump-out phenomenon is the following phenomenon: the thermally conductive silicone composition applied to the substrate (e.g., a heating element) or the thermally conductive member after curing flows out from the gap between the heating element and the heat sink, thereby generating cracks and voids. Before or during curing, at least a portion of the thermally conductive silicone composition may flow. After the thermally conductive silicone composition is cured, the thermally conductive silicone composition may expand or contract due to vibration or heat, thereby causing outflow. In all cases of this phenomenon, the thermal resistance of the thermally conductive member increases, thereby reducing the heat dissipation performance.
[0034] Component (B): Component (B) is an organopolysiloxane having two or more hydrogen atoms (two or more hydrosilyl groups) bonded to silicon atoms. Component (B) may have a viscosity and a degree of polymerization that are not limited to specific values and may be selected according to the desired mixed viscosity of the thermally conductive silicone composition. For example, component (B) may have a viscosity of 10 mPa·s or more and 10,000 mPa·s or less at 25°C. Component (B) is an organopolysiloxane having two hydrogen atoms bonded to silicon atoms in one molecule, and serves as a crosslinking agent for curing the thermally conductive silicone composition of the present invention. The number of hydrogen atoms bonded to the silicon atom is not particularly limited as long as it is 2 or more, and the number may be 2 or more and 4 or less. It is particularly preferred that the linear component (B) has hydrogen atoms bonded to each silicon atom at both molecular chain ends, and the component (B) may have two hydrogen atoms bonded to the same silicon atom in the molecule.
[0035] Component (B) may be any organopolysiloxane as long as it contains two hydrogen atoms bonded to silicon atoms (two hydrosilyl groups) in one molecule. Examples of organopolysiloxanes that can be used include methylhydrogenpolysiloxane, dimethylsiloxane-methylhydrogensiloxane copolymers, methylphenylsiloxane-methylhydrogensiloxane copolymers, cyclic methylhydrogenpolysiloxane, and organopolysiloxanes composed of dimethylhydrogensiloxy units and SiO 4 / 2 As component (B), one type thereof may be used alone, or two or more types thereof may be used in combination as appropriate.
[0036] The molecular structure of component (B) is not particularly limited and may be, for example, a linear, branched, cyclic or three-dimensional network structure. Specifically, a structure represented by the following average composition formula (2) may be used: R 3 p H q SiO (4-p-q) / 2 (2) In formula (2), R 3 is an unsubstituted or substituted monovalent hydrocarbon group other than an aliphatic unsaturated hydrocarbon group, p is 0 to 3.0, preferably 0.7 to 2.1, q is 0.0001 to 3.0, preferably 0.001 to 1.0, and p+q is a positive number satisfying 0.5 to 3.0, preferably 0.8 to 3.0. ).
[0037] In formula (2), R 3 Examples include unsubstituted or halogen-substituted monovalent hydrocarbon groups having 1 to 10 carbon atoms, preferably 1 to 8 carbon atoms, etc., but do not include aliphatic unsaturated hydrocarbon groups. Specific examples thereof include: alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, isopropyl, isobutyl, tert-butyl and cyclohexyl; aryl groups such as phenyl, tolyl and xylyl; aralkyl groups such as benzyl and phenethyl; and halogenated alkyl groups such as 3-chloropropyl and 3,3,3-trifluoropropyl. Among them, methyl, ethyl, propyl, phenyl and 3,3,3-trifluoropropyl are preferred, and methyl is particularly preferred.
[0038] Specific examples of component (B) include 1,1,3,3-tetramethyldisiloxane, 1,3,5,7-tetramethylcyclotetrasiloxane, methylhydrogencyclopolysiloxane, methylhydrogensiloxane-dimethylsiloxane cyclic copolymer, tris(dimethylhydrogensiloxy)methylsilane, tris(dimethylhydrogensiloxy)phenylsilane, dimethylsiloxane-methylhydrogensiloxane copolymer with both molecular chain ends capped with dimethylhydrogensiloxy groups, methylhydrogenpolysiloxane with both molecular chain ends capped with dimethylhydrogensiloxy groups, and methylhydrogenpolysiloxane with both molecular chain ends capped with trimethylsiloxy groups. Siloxane, dimethylpolysiloxane having both molecular chain ends terminated by dimethylhydrogensiloxy groups, dimethylsiloxane-diphenylsiloxane copolymer having both molecular chain ends terminated by dimethylhydrogensiloxy groups, dimethylsiloxane-methylhydrogensiloxane copolymer having both molecular chain ends terminated by trimethylsiloxy groups, dimethylsiloxane-diphenylsiloxane-methylhydrogensiloxane copolymer having both molecular chain ends terminated by trimethylsiloxy groups, dimethylsiloxane-methylhydrogensiloxane copolymer having both molecular chain ends terminated by dimethylhydrogensiloxy groups, H(CH 3 ) 2 SiO 1 / 2 Unit and SiO 2 Unit copolymer, H(CH 3 ) 2 SiO 1 / 2 Unit and (CH 3 ) 3 SiO 1 / 2 Unit and SiO 2 units, and mixtures of two or more of these organopolysiloxanes.
[0039] In the above silicone composition, the content of component (B) is preferably such that the ratio of the number of hydrosilyl groups in component (B) to the number of alkenyl groups in component (A) is 1 / 5 to 7, more preferably 1 / 3 to 2, and more preferably 2 / 5 to 5 / 4. When the content of component (B) falls within the above range, the thermally conductive silicone composition is sufficiently cured, and the hardness of the entire thermally conductive silicone composition falls within a more preferred range, so that when the thermally conductive member obtained by curing the thermally conductive silicone composition is used as a gap filler, cracks are less likely to occur. In addition to this, there is an advantage that the thermally conductive silicone composition does not sag, and even when the substrate to which the composition has been applied is set in a vertical orientation (standing upright), its holding ability in the vertical direction can be maintained.
[0040] The hydrosilyl group in component (B) may be present at the molecular chain terminal, may be present in the side chain, or may be present in both the molecular chain terminal and the side chain. It is preferred to use a mixture of an organopolysiloxane having a hydrosilyl group only at the molecular chain terminal and an organopolysiloxane having a hydrosilyl group only in the side chain of the molecular chain.
[0041] Component (B) may be an organopolysiloxane in which hydrogen atoms are bonded to silicon atoms only at two molecular chain ends. An organopolysiloxane having a hydrosilyl group at each of the two molecular chain ends has a low hydrosilyl content, thereby improving the flexibility of the thermally conductive member obtained after curing, and further advantageously enhancing the adhesion to the substrate. The organopolysiloxane having a hydrosilyl group only at the molecular chain end has an advantage in that the organopolysiloxane has high reactivity due to low steric hindrance, while the organopolysiloxane having a hydrosilyl group in a side chain contributes to the construction of a network by a cross-linking reaction, and thus has an advantage in that the strength of the thermally conductive member is improved. In order to impart flexibility to the thermally conductive member after curing, it is preferred to use an organopolysiloxane having a hydrosilyl group only at the molecular chain end.
[0042] From the viewpoint of improving adhesive properties and heat resistance, component (B) may contain an organohydrogenpolysiloxane having trimethylsiloxy groups at both molecular chain ends of the organohydrogenpolysiloxane and containing at least one aryl group in the molecule. For economic reasons, the aryl group is more preferably a phenyl group. An organohydrogenpolysiloxane containing an aryl group and an organohydrogenpolysiloxane not containing an aryl group may be used in combination.
[0043] The viscosity of component (B) at 25° C. is 10 mPa·s or more and 10,000 mPa·s or less, preferably 20 mPa·s or more and 5,000 mPa·s or less, and more preferably 30 mPa·s or more and 2,000 mPa·s or less. In order to adjust the viscosity of the thermally conductive silicone composition as a final product, two or more types of organopolysiloxanes having hydrogen atoms and having respective different viscosities may also be used. The mixed viscosity of the thermally conductive silicone composition may be 10 Pa·s or more and 1,000 Pa·s or less, more preferably 20 Pa·s or more and 500 Pa·s or less, and even more preferably 30 Pa·s or more and 250 Pa·s or less.
[0044] The content of the organopolysiloxane of component (B) is preferably 10 parts by mass or more and 98 parts by mass or less, and more preferably 20 parts by mass or more and 90 parts by mass or less, based on 100 parts by mass of the total amount of component (A) and component (B) in the thermally conductive silicone composition of the present invention. When the content falls within the above range, the hardness of the cured thermally conductive silicone composition can fall within an appropriate range. In addition, the thermally conductive member can exhibit flexibility and stability after curing.
[0045] Component (C): The silanol group-containing organopolysiloxane having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C. as component (C) is added to improve the storage stability of the thermally conductive silicone composition and also to improve the flexibility and pump-out resistance of a thermally conductive member obtained by curing the composition. Component (C) may be a compound having neither an alkenyl group nor a hydrogen atom (hydrosilyl group) bonded to a silicon atom. Component (C) may be a linear organopolysiloxane having at least one silanol group at each molecular chain end. If component (C) has such a structure, component (A) and component (B) do not participate in a crosslinking reaction, and therefore, the flexibility of the thermally conductive member is improved.
[0046] Component (C) is an organopolysiloxane having at least two silanol groups (hydroxyl groups directly bonded to silicon atoms in one molecule). Except for the hydroxyl groups directly bonded to the silicon atoms, the monovalent organic groups are not particularly limited, and examples thereof include monovalent hydrocarbon groups having 1 to 10 carbon atoms. Specifically, examples include: alkyl groups such as methyl, ethyl, propyl and butyl groups; cycloalkyl groups such as cyclopentyl and cyclohexyl groups; aryl groups such as phenyl and naphthyl groups; and alkenyl groups such as vinyl and propenyl groups. In the present invention, specifically, 80 mol% or more of the organic groups other than the silanol groups are preferably methyl groups. More preferably, the compound does not contain alkenyl groups. There is no particular limitation on the molecular structure, and in principle, a linear structure is preferred industrially, and a branched structure may also be used. The viscosity of component (C) at 25° C. is preferably 10 mPa·s or more and 500 mPa·s or less, more preferably 30 mPa·s or more and 500 mPa·s or less.
[0047] The content of the silanol group in component (C) may be 1% by mass or more and 10% by mass or less, based on the total content of component (C) as 100% by mass. The content of the silanol group is more preferably 1% by mass or more and 8% by mass or less, and even more preferably 1% by mass or more and 5% by mass or less. Here, the content of silanol groups is determined according to the following formula: [mass of silanol groups in molecule] / [total mass per molecule of component (C)]×100 (mass %). When the silanol group content falls within the above range, the effect of suppressing precipitation of the thermally conductive filler is particularly high.
[0048] A single type of compound may be used as component (C), or a mixture of two or more types of compounds may be used.
[0049] The silanol group-containing organopolysiloxane (C) is not particularly limited, and any known silanol group-containing organopolysiloxane may be used as appropriate. As such a silanol group-containing organopolysiloxane, commercially available products may be suitably used, and, for example, alkenyl-free dimethylsilanol-terminated polydimethylsiloxane may be obtained from Wacker Chemie AG.
[0050] The silanol groups in component (C) interact with the OH groups on the surface of the thermally conductive filler, which will be described later. In addition, since component (C) has a silicone skeleton, it has good compatibility with components (A) and (B). Through these effects, component (C) suppresses the phenomenon that the thermally conductive filler precipitates in the thermally conductive silicone composition over time. Therefore, compared to the case where component (C) is not added, even if the thermally conductive silicone composition is stored for a long time, a thermally conductive member in which the distribution of the components in the composition is prevented from becoming uneven and stable quality is maintained for a long time can be obtained.
[0051] Based on the total amount of component (A) and component (B) as 100 parts by mass, the amount of component (C) added is 3 parts by mass or more and 100 parts by mass or less, preferably 5 parts by mass or more and 100 parts by mass or less, and more preferably 10 parts by mass or more and 50 parts by mass or less. When the amount falls within the above range, flexibility, adhesion and low mixed viscosity can be achieved while suppressing precipitation. Specifically, when the thermally conductive member is used as a gap filler, the thermally conductive silicone composition can be injected into a small gap and has the advantage of excellent crushing performance. In addition, the pump-out resistance of the thermally conductive member is maintained after curing, and the low hardness can be maintained. The cured thermally conductive member is therefore able to impart flexibility to the thermally conductive member after curing. When the pump-out resistance is indicated as a value less than 110% according to the following measurement method, the pump-out resistance is determined to be favorable.
[0052] When the amount of component (C) added exceeds 3 parts by mass, the pump-out resistance is particularly favorable. When the amount is 5 parts by mass or more, the pump-out resistance is more favorable. When the amount is 50 parts by mass or more, the pump-out resistance is further more favorable. The thermally conductive silicone composition of the present invention may contain an organopolysiloxane having no silanol group, alkenyl group or hydrosilyl group (e.g., non-functionalized dimethylsiloxane) as appropriate. In this case, when the proportion of component (C) is 50% by mass or more in the total amount of the organopolysiloxane not involved in the crosslinking reaction of component (A) with component (B) (i.e., the organopolysiloxane having no alkenyl group or hydrosilyl group), the pump-out resistance can be further enhanced.
[0053] When the amount of component (C) added increases, flexibility is enhanced, the effect of suppressing precipitation is improved, and crushing after solidification can be easily performed. When the amount of component (C) is further increased, for example, when the amount of component (C) is increased to 50 parts by mass or more based on 100 parts by mass of the total amount of component (A) and component (B), the needle penetration can be improved. For example, the needle penetration after curing at 23° C. for 24 hours can be increased to 10 or more, which is more preferred.
[0054] Although component (C) has a low viscosity, component (C) has a property that the adhesion to the substrate after curing of the thermally conductive silicone composition is less likely to decrease than when a polysiloxane having no silanol group is mixed. Therefore, even when component (C) is added in an amount of 50 parts by mass or more based on 100 parts by mass of the total amount of component (A) and component (B), suitable adhesion can be maintained. Component (C) may enhance thread breakage when the thermally conductive silicone composition before curing is applied to a substrate using a device such as a dispenser.
[0055] Component (D): The addition reaction catalyst of component (D) is a catalyst that promotes the addition-curing reaction between the alkenyl group bonded to the silicon atom in the above-mentioned component (A) and the hydrogen atom bonded to the silicon atom in the above-mentioned component (B), and is a catalyst known to those skilled in the art. Examples of component (D) include platinum group metals, such as platinum, rhodium, palladium, osmium, iridium and ruthenium; and catalysts in which any of the above-mentioned metals is supported by a particulate supporting material (e.g., activated carbon, alumina and silicon oxide). In addition, examples of component (D) include platinum halides, platinum-olefin complexes, platinum-alcohol complexes, platinum-alcoholate complexes, platinum-vinylsiloxane complexes, dicyclopentadiene-dichloroplatinum, cyclooctadiene-dichloroplatinum, and cyclopentadiene-dichloroplatinum.
[0056] In addition, from an economic point of view, a metal compound catalyst other than the above-mentioned platinum group metal can be used as component (D). Examples of iron catalysts for hydrosilylation include iron-carbonyl composite catalysts, iron catalysts with cyclopentadienyl as ligands, iron catalysts with a combination of terpyridine ligands or terpyridine ligands and bistrimethylsilylmethyl, iron catalysts with bisiminopyridine ligands, iron catalysts with bisiminoquinoline ligands, iron catalysts with aryl as ligands, iron catalysts with cyclic or acyclic olefin groups with unsaturated groups, and iron catalysts with cyclic or acyclic olefin groups with unsaturated groups. Other examples of catalysts for hydrosilylation include cobalt catalysts, vanadium catalysts, ruthenium catalysts, iridium catalysts, samarium catalysts, nickel catalysts, and manganese catalysts.
[0057] In terms of the concentration of the catalyst metal element, the amount of component (D) added is preferably 0.5 ppm or more and 1,000 ppm or less, more preferably 1 ppm or more and 500 ppm or less, and still more preferably 1 ppm or more and 100 ppm or less, based on the total mass of the thermally conductive silicone composition, although an effective amount thereof is used depending on the curing temperature and curing time required depending on the application used. If the amount is less than 0.5 ppm, the addition reaction becomes extremely slow. If the amount exceeds 1,000 ppm, it is economically undesirable due to increased costs.
[0058] Component (E): The thermally conductive filler of component (E) is a filler material component that improves the thermal conductivity of the thermally conductive silicone composition. The thermally conductive filler used in the present invention is one or more types selected from the following group: metal, metal oxide, metal hydroxide, metal nitride, and metal carbide, and has a 30m 2 / g or less, and an average particle size of 1 μm to 100 μm. On the surface of these types of thermally conductive fillers, OH groups are generated due to reaction with atmospheric water. The surface OH groups are uniformly dispersed in the thermally conductive silicone composition by interaction with component (C), and the thermally conductive filler hardly precipitates even under long-term storage. This is believed to be due to hydrogen bonds formed by OH groups on the surface of the thermally conductive filler and silanol groups of component (C), and the fact that all components (A), (B) and (C) have a siloxane skeleton and are highly compatible with each other.
[0059] The thermally conductive filler may be added in an amount required to increase the thermal conductivity of the thermally conductive member (for example, 2.0 W / m·K or more), and for example, the content of component (E) is preferably 300 parts by mass or more and 2,000 parts by mass or less, more preferably 400 parts by mass or more and 1,900 parts by mass or less, and even more preferably 500 parts by mass or more and 1,800 parts by mass or less, based on 100 parts by mass of the total amount of component (A) and component (B). When the content of component (E) falls within the above range, the thermally conductive silicone composition as a whole has sufficient thermal conductivity, is easy to mix when blended, and maintains flexibility even after curing. In addition, since the component (E) included in this amount does not excessively increase the specific gravity, the resulting composition is more suitable as a thermally conductive silicone composition for forming a thermally conductive member that requires high thermal conductivity and weight reduction. If the content of component (E) is too little, it becomes difficult to sufficiently improve the thermal conductivity of the cured product obtained from the thermally conductive silicone composition, and if the content of component (E) is too much, the resulting silicone composition becomes highly viscous, and it is likely to become difficult to uniformly apply the thermally conductive silicone composition, resulting in problems such as an increase in the thermal resistance value of the cured product and a decrease in the flexibility of the cured product.
[0060] The shape of the thermally conductive filler is not particularly limited as long as the BET specific surface area is 30 m 2 / g or less. For example, the shape of the thermally conductive filler may be spherical, amorphous, fine powder, fiber, scale shape, or the like. In order to add the thermally conductive filler in an amount required to improve the thermal conductivity of the thermally conductive member, the thermally conductive filler preferably has a spherical shape, and the average particle size may be 1 μm to 100 μm. In this article, the spherical shape may be not only a true spherical shape but also a round shape. Compared with thermal conductive fillers having a larger specific surface area, the BET specific surface area is 30 m 2 / g or less of a thermally conductive filler is more likely to precipitate in a liquid containing a polymer (eg, component (A) and component (B)). In the present invention, the mixed component (C) suppresses precipitation of the thermally conductive filler.
[0061] The thermally conductive filler preferably has a thermal conductivity of 10 W / m·K or more. If the thermal conductivity is less than 10 W / m·K, the thermal conductivity of the thermally conductive silicone composition itself may be reduced. Specifically, if the thermally conductive member needs to be electrically insulated, it is conceivable to select a non-conductive thermally conductive filler.
[0062] Component (E) may preferably be a metal oxide, a metal hydroxide, a nitride or a mixture thereof, and in some cases may be an amphoteric hydroxide or an amphoteric oxide. Specifically, one or more types selected from the following group are preferably used: aluminum oxide, aluminum hydroxide, magnesium oxide, magnesium hydroxide, zinc oxide, aluminum nitride and boron nitride. Among them, component (E) preferably contains at least one selected from aluminum hydroxide and aluminum oxide. It should be noted that alumina is an insulating material, has relatively good compatibility with component (A) and component (B), can be selected from a variety of particle sizes in the industry, is an easily available resource, is relatively cheap, and is therefore suitable as a thermally conductive inorganic filler material. When spherical alumina is used as component (E), α-alumina obtained by high-temperature thermal spraying or hydrothermal treatment of alumina hydrate may be used.
[0063] The average particle size of component (E) is 1 μm or more and 100 μm or less, more preferably 2 μm or more and 80 μm or less, and even more preferably 2 μm or more and 70 μm or less. If the average particle size is too small, the fluidity of the thermally conductive silicone composition is reduced. If the average particle size is too large, the dispensing properties are impaired, and problems such as scratching of the coating device due to the filler being caught by the sliding part of the coating device may occur. In the present invention, the average particle size of component (E) is defined by D50 (or median diameter), which is the 50% particle size in the volume-based cumulative particle size distribution measured by a laser diffraction particle size measuring device.
[0064] As component (E), a spherical thermally conductive filler may be used, or a thermally conductive filler other than a spherical shape (e.g., an amorphous shape, a powder shape, a fiber shape, or a plate shape) may be used in combination. When two or more types of thermally conductive fillers having different shapes are used in combination, the composition can be filled with the filler in an almost densely packed state, so that the thermal conductivity is further improved advantageously. In the case of using a spherical thermally conductive filler in combination with a thermally conductive filler other than a spherical filler, when the proportion of the spherical thermally conductive filler is 30 parts by mass or more relative to 100% by mass of the total component (E), the thermal conductivity can be further improved.
[0065] The BET specific surface area of component (E) is 30 m 2 For example, when component (E) is a spherical filler, the BET specific surface area is preferably 1 m 2 / g or less, and more preferably 0.5m 2 When a non-spherical thermally conductive filler is used in combination, the BET specific surface area of the non-spherical filler may be, for example, 5 m 2 / g or less, and more preferably 3m 2 / g or less.
[0066] In the thermally conductive silicone composition according to the present invention, fillers other than component (E) may be further added. Examples of fillers other than component (E) may include: fillers without thermal conductivity, such as fumed silica, crystalline silica, precipitated silica, hollow fillers, silsesquioxane, magnesium carbonate, calcium carbonate, zinc carbonate, layered mica, carbon black, diatomaceous earth, glass fiber, silicone rubber powder, and silicone resin powder; and fillers with a BET specific surface area of 50 m 2 / g or more thermally conductive filler. When the mixed BET specific surface area is greater than 50 m 2 / g of filler, the viscosity of the thermally conductive silicone composition increases, the adhesion of the cured thermally conductive silicone composition to the substrate is impaired, and the flexibility tends to decrease. Therefore, the heat dissipation performance may be reduced. When the composition is densely filled with a large volume of filler, the movement of the silicone rubber molecules in the composition is hindered and the elasticity is impaired. Based on the total amount of component (A) and component (B) as 100 parts by mass, the BET specific surface area is 50m 2 The content of the filler of 100 g / cm2 or more in the thermally conductive silicone composition according to the present invention needs to be 3 parts by mass or less. In the present invention, the BET specific surface area of component (E) is a value obtained by measuring the amount of gas physically adsorbed to the surface of particles in a low temperature state and calculating the specific surface area.
[0067] Component (F): An organohydrogenpolysiloxane may be used as the crosslinking agent (F). Component (F) forms a cured product by an addition reaction with an alkenyl group, and may have a hydrogen atom (hydrogen silyl group) bonded to one or more silicon atoms in a side chain within the molecule. The crosslinking agent (F) preferably has three or more hydrosilyl groups in one molecule, and has at least one hydrosilyl group in a side chain within the molecule. The crosslinking agent of the present invention is more preferably an organohydrogenpolysiloxane having 5 or more hydrosilyl groups, and may have 10 or more and 15 or less hydrosilyl groups. The organohydrogenpolysiloxane as a crosslinking agent has at least two hydrosilyl groups present in its side chain. The number of hydrosilyl groups at the end of a molecular chain may be 0 or more and 2 or less, and is preferably 2 in terms of cost. The molecular structure of the organohydrogenpolysiloxane may be any one of a linear, cyclic, branched, and three-dimensional network structure. The position of the silicon atom bonded to the hydrogen atom is not particularly limited, and may be located at the end of the molecular chain, at a non-terminal molecular chain site (in the middle of the molecular chain), or in a side chain. Other conditions in the organohydrogenpolysiloxane used as a crosslinking agent, the type of organic group other than the hydrosilyl group, the bonding position, the degree of polymerization, the structure, etc. are not particularly limited. Two or more types of organohydrogenpolysiloxanes may be used.
[0068] The crosslinking agent (F) may be added in an amount necessary for forming a matrix comprising component (A) and component (B) by crosslinking. For example, the amount of component (F) added may be 1 part by mass or more and 10 parts by mass or less, more preferably 1 part by mass or more and 6 parts by mass or less, and even more preferably 1 part by mass or more and 4 parts by mass or less, based on 100 parts by mass of the total amount of component (A) and component (B).
[0069] In the thermally conductive silicone composition of the present invention, as an additional optional component other than the aforementioned components (A) to (F), conventionally known additives used in silicone rubber or gel can be used as long as the purpose of the present invention is not impaired. Examples of such additives include: organic silicon compounds or organic siloxanes (also called silane coupling agents) that generate silanols by hydrolysis, condensation catalysts, adhesion aids, pigments, dyes, curing inhibitors, heat resistance imparting agents, flame retardants, antistatic agents, conductivity imparting agents, air tightness improvers, radiation shielding agents, electromagnetic wave shielding agents, preservatives, stabilizers, organic solvents, plasticizers, fungicides, organic polysiloxanes containing one hydrogen atom or alkenyl group bonded to a silicon atom in one molecule and no other functional groups, and non-functional organic polysiloxanes containing neither hydrogen atoms bonded to silicon atoms nor alkenyl groups bonded to silicon atoms. As these optional components, one type thereof can be used alone, or two or more types thereof can be used in combination as appropriate.
[0070] Examples of the silane coupling agent include organic silicon compounds and organic siloxanes having an organic group and an alkoxy group bonded to a silicon atom in one molecule, wherein the organic group includes an epoxy group, an alkyl group, an aryl group, a vinyl group, a styryl group, a methacryloyl group, an acryl group, an amino group, an isocyanurate group, an ureide group, a mercapto group, an isocyanate group, and an acid anhydride. An example of a silane coupling agent is a silane compound, such as octyl trimethoxysilane, octyl triethoxysilane, decyl trimethoxysilane, decyl triethoxysilane, dodecyl trimethoxysilane, dodecyl triethoxysilane, vinyl trimethoxysilane, 3-glycidyloxypropyl trimethoxysilane, p-phenylene trimethoxysilane, 3-methacryloxypropyl trimethoxysilane, 3-acryloxypropyl trimethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl triethoxysilane, tris-(trimethoxysilyl propyl) isocyanurate, 3-ureidopropyl trialkoxysilane, 3-mercaptopropyl methyl dimethoxysilane, 3-isocyanatopropyl triethoxysilane, and 3-trimethoxysilyl propyl succinic anhydride. The silane compound may be a compound not containing a hydrosilyl group. One type thereof may be used alone, or two or more types thereof may be used in combination as appropriate. When the surface of the thermally conductive filler is treated with a silane coupling agent, the affinity with the silicone polymer may be improved, the viscosity of the composition may be reduced, and the filling properties of the thermally conductive filler may be improved. Therefore, when a larger amount of filler is added, the thermal conductivity may be improved. The silanol generated by the hydrolysis can react with and bond to a condensable group (e.g., a hydroxyl group, an alkoxy group, an acid group, etc.) present on the surface of a metal substrate or an organic resin substrate. The silanol and the condensable group react and bond to each other via the catalytic action of a condensation catalyst to be described later, thereby promoting adhesion of the thermally conductive member to various substrates. As the amount of the silane coupling agent added relative to the amount of the thermally conductive filler, an effective amount is used according to the curing temperature or curing time required depending on the application used. The general optimal amount is usually 0.5 wt % or more and 2 wt % or less relative to the amount of the thermally conductive filler. The standard of the required amount is calculated by the following expression. The silane coupling agent can be added in an amount of 1 to 3 times the standard of the required amount: The required amount of silane coupling agent (g) = the mass of thermal conductive filler (g) × the specific surface area of thermal conductive filler (m 2 / g) / Minimum coverage area of silane coupling agent (m 2 / g)
[0071] If necessary, a condensation catalyst may be used together with the above-mentioned silane coupling agent. As a condensation catalyst, a compound selected from the following metals can be used: magnesium, aluminum, titanium, chromium, iron, cobalt, nickel, copper, zinc, zirconium, tungsten and bismuth. Preferred examples of condensation catalysts include metal compounds, such as organic acid salts, alkoxides and chelate compounds of trivalent aluminum, trivalent iron, trivalent cobalt, divalent zinc, tetravalent zirconium and trivalent bismuth. Specific examples thereof include organic acids, such as octanoic acid, lauric acid and stearic acid; alkoxides, such as propoxides and butoxides; and polydentate ligand chelate compounds, such as catechol, crown ethers, polyvalent carboxylic acids, hydroxy acids, diketones and keto acids. Here, various types of ligands can be bonded to one metal. Specifically, it is preferred that compounds of zirconium, aluminum or iron are likely to produce stable curability even when the chemical composition and conditions of use are slightly different. In addition, examples of more desirable compounds include zirconium butoxide and aluminum or iron trivalent chelate compounds, including multidentate ligands such as malonate, acetoacetate, acetylacetone or substituted derivatives thereof. In the case of trivalent aluminum or iron metal compounds, organic acids having 5 to 20 carbon atoms, such as octanoic acid, can be preferably used. The multidentate ligand and the organic acid can be bonded to one metal, and the resulting structure can also be used.
[0072] Examples of the above-mentioned substituted derivatives include derivatives in which hydrogen atoms contained in the above-mentioned compounds are substituted by the following groups: alkyl groups, such as methyl or ethyl groups; alkenyl groups, such as vinyl or allyl groups; aryl groups, such as phenyl groups; halogen atoms, such as chlorine atoms or fluorine atoms; hydroxyl groups; fluoroalkyl groups; ester group-containing groups; ether group-containing groups; ketone group-containing groups; amino group-containing groups; amido group-containing groups; carboxylic acid group-containing groups; nitrile group-containing groups; epoxy group-containing groups, etc. Specific examples thereof include 2,2,6,6-tetramethyl-3,5-heptanedione and hexafluoropentanedione.
[0073] As the adhesion aid, an adhesion aid having an alkoxy group in the molecule is preferred, and specifically, tetraethoxysilane is preferred. Other preferred examples of the adhesion aid include 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, oligomers of 3-glycidyloxypropyltrimethoxysilane, oligomers of 3-glycidyloxypropyltriethoxysilane; and an adhesion aid having one or more groups selected from vinyl, methacryloyl, acryloyl and isocyanate groups as organic functional groups. Further examples thereof include methacryloxysilanes, such as 3-methacryloyloxypropyltrimethoxysilane and 3-methacryloyloxypropyltriethoxysilane; 3-trimethoxysilylpropylsuccinic anhydride; and furandiones, such as dihydro-3-(3-(triethoxysilyl)propyl)-2,5-furandione). The organic functional group can be bonded to the silicon atom through another group such as an alkylene group. In addition to the above substances, an organosilicon compound or organosiloxane containing an organic group (e.g., an epoxy group, an alkyl group or an aryl group) and an alkoxy group bonded to a silicon atom in one molecule is also preferred. In addition, an organosilicon compound or organosiloxane having at least one organic group (e.g., an epoxy group, an alkyl group or an aryl group) and at least two alkoxy groups bonded to a silicon atom in one molecule is preferred. Such an epoxy group can be bonded to the silicon atom in the form of a glycidyloxyalkyl group (e.g., a glycidyloxypropyl group) or an epoxy-containing cyclohexylalkyl group (e.g., 2,3-epoxycyclohexylethyl or 3,4-epoxycyclohexylethyl). Alternatively, an organic group having a straight or branched alkyl group containing 1 to 20 carbon atoms, or an aromatic ring is preferred. If an epoxy group is contained, two to three epoxy groups may be contained in one molecule. Preferred examples of the alkoxy group bonded to the silicon atom include a methoxy group, an ethoxy group, a propoxy group, and an alkyldialkoxysilyl group, such as a methyldimethoxysilyl group, an ethyldimethoxysilyl group, a methyldiethoxysilyl group, and an ethyldiethoxysilyl group. As the functional group other than the above functional groups, for example, a functional group selected from an alkenyl group (eg, vinyl group), a (meth)acryloyloxy group, a hydrosilyl group (SiH group), and an isocyanate group can be used.
[0074] Examples of the pigment include titanium oxide, aluminum oxide silicate, iron oxide, zinc oxide, calcium carbonate, carbon black, rare earth oxides, chromium oxide, cobalt pigments, ultramarine blue, cerium silanol, aluminum oxide, aluminum hydroxide, titanium yellow, barium sulfate, precipitated barium sulfate, and mixtures thereof. The amount of the pigment added is preferably 0.001% to 5% based on the total mass of the thermally conductive silicone composition, but an effective amount thereof is also used depending on the curing temperature and curing time required for the application used. The amount of the pigment is preferably 0.01% or more and 2% or less, and more preferably 0.05% or more and 1% or less. If the amount is less than 0.001%, the resulting composition is not sufficiently colored, so it is difficult to visually distinguish the first liquid from the second liquid. On the other hand, if the amount exceeds 5%, the cost will increase, which is economically undesirable.
[0075] The curing inhibitor has the ability to adjust the curing rate of the addition reaction, and any curing inhibitor conventionally known in the art can be used as a compound having a curing inhibition effect. Examples thereof include acetylene compounds, hydrazines, triazoles, phosphines, and thiols. Specific examples of such compounds include: phosphorus-containing compounds such as triphenylphosphine; nitrogen-containing compounds such as tributylamine, tetramethylethylenediamine, and benzotriazole; sulfur-containing compounds; acetylene compounds; compounds containing two or more alkenyl groups; hydroperoxides; maleic acid derivatives; and silane and silicone compounds having amino groups. The amount of the curing inhibitor added is preferably 0.1 to 15 parts by mass based on 100 parts by mass of the total amount of component (A) and component (B), but an effective amount thereof is also used depending on the curing temperature and curing time required for the application used. The amount is preferably 0.2 to 10 parts by mass, and more preferably 0.5 to 5 parts by mass. If the amount is less than 0.1 parts by mass, the addition reaction becomes significantly accelerated, and the curing reaction proceeds during coating, which may deteriorate the processability. On the other hand, if the amount exceeds 10 parts by mass, the addition reaction becomes slow, and thus a pumping phenomenon may occur.
[0076] Specific examples of cure inhibitors include various "ene-yne" systems, such as 3-methyl-3-pentene-1-yne and 3,5-dimethyl-3-hexene-1-yne; alkynols, such as 3,5-dimethyl-1-hexin-3-ol, 1-ethynyl-1-cyclohexanol and 2-phenyl-3-butyn-2-ol; well-known maleates and fumarates, such as dialkyl maleates, dienyl maleates, dialkoxyalkyl maleates, dialkyl fumarates, dienyl fumarates and dialkoxyalkyl fumarates; and cure inhibitors containing cyclovinylsiloxanes.
[0077] Examples of the heat resistance-imparting agent include cerium hydroxide, cerium oxide, iron oxide, fumed titanium dioxide, and mixtures thereof.
[0078] As the airtightness improving agent, any agent can be used as long as it has the effect of reducing the air permeability of the cured product, and any organic or inorganic substance can be used. Specific examples thereof include urethane, polyvinyl alcohol, polyisobutylene, isobutylene-isoprene copolymer, talc having a plate-like shape, mica, glass flakes, diaspore, various metal foils and metal oxide powders, and mixtures thereof.
[0079] The thermally conductive silicone composition according to the present invention may not contain an organosilicon compound having one or more alkenyl groups and one or more alkoxy groups bonded to a silicon atom in one molecule. When a compound having an alkenyl group and an alkoxy group bonded to a silicon atom in one molecule is contained in the composition, when the thermally conductive member is used as a gap filler, the compound serves as a component that bonds the substrate to the gap filler. When the thermally conductive member is exposed to high temperatures and peeled off from the substrate, the composition according to the present invention that does not contain such a component can further reduce deformation, damage, etc. of the battery, etc.
[0080] The thermally conductive silicone composition of the present invention may contain any one or two or more selected from the following group: octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), dodecamethylcyclohexasiloxane (D6), tetradecamethylcycloheptasiloxane (D7), and hexadecamethylcyclooctasiloxane (D8). Based on 100 parts by mass of the total amount of component (A) and component (B), the total content of (D4), (D5), (D6), (D7) and (D8) may be less than 0.1 parts by mass (ie, less than 1,000 ppm). When the total content of (D4) to (D8) contained in the thermally conductive silicone composition falls within the above range, the flash point of the entire composition can be increased, and the safety during storage can be improved. In addition, the thermally conductive member obtained by curing the composition can be arranged in a manner that makes it less likely to cause contact failure with electronic components and the like. A thermally conductive silicone composition comprising (D4) to (D8) in an amount of less than 0.1 parts by mass as the total content of (D4) to (D8), based on 100 parts by mass of the total amount of component (A) and component (B), can be produced using component (A) in which the total content of (D4) to (D8) is less than 0.1 parts by mass, component (B) in which the total content of (D4) to (D8) is less than 0.1 parts by mass, and component (C) in which the total content of (D4) to (D8) is less than 0.1 parts by mass. The respective contents of (D4) to (D8) are measured by gas chromatography. The measurement conditions of the gas chromatography can be appropriately selected according to a conventionally known method.
[0081] The use of components (A), (B) and (C) in which the total content of (D4) to (D8) is small can make the total content of (D4) to (D8) in the thermally conductive silicone composition fall within the aforementioned range. As a method for reducing the content of (D4) to (D8) in components (A) to (C), a method of heat-treating the components under reduced pressure is well known. For example, preferably, during the production of the raw materials of components (A) to (C), a heat treatment is performed at 180° C. and 20 mmHg under reduced pressure for about 8 hours.
[0082] The thermally conductive silicone composition according to the present invention is an addition-curable composition and may be a one-component composition or a two-component composition. When the composition is appropriately designed to be cured by heating, the one-component composition may have improved storage properties. In the case of a two-component composition, storage stability can be further improved without these designs, and a composition that cures at room temperature (e.g., 25° C.) can be easily obtained. In this case, the thermally conductive silicone composition according to the present invention can be dispensed into a first liquid and a second liquid, for example, as follows. The first liquid does not contain component (B) but contains component (D), and the second liquid contains components (B) and (F) but does not contain component (D).
[0083] Therefore, the method for producing a two-component thermally conductive silicone composition according to the present invention comprises: In a first step, a component (A) of an alkenyl-containing organopolysiloxane, a component (C) of an organopolysiloxane containing a silanol group having a viscosity of 10 to 500 mPa·s at 25° C., a component (E) of a thermally conductive filler, and a component (D) of an addition reaction catalyst are mixed to obtain a first liquid; and In the second step, a component (A) of an alkenyl group-containing organopolysiloxane, a component (B) of an organopolysiloxane having two or more hydrosilyl groups in one molecule, a component (C) of an organopolysiloxane containing a silanol group having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C., a component (E) of a thermally conductive filler, and a component (F) of a cross-linking agent are mixed to obtain a second liquid.
[0084] Since the precipitation of the thermally conductive filler is suppressed, the thermally conductive silicone composition has high storage stability. For example, when the thermally conductive silicone composition is stored at room temperature for 1,000 hours, the difference in specific gravity between the upper portion and the lower portion of the thermally conductive silicone composition is within 0.2.
[0085] The present invention also provides a method for producing a thermally conductive member, the method comprising: a mixing step of mixing a first liquid and a second liquid of the above-mentioned two-component thermally conductive silicone composition; an applying step of applying the mixture of the first liquid and the second liquid obtained in the mixing step to a substrate; and a curing step of curing the uncured mixture applied in the applying step.
[0086] The thermally conductive silicone composition applied to the substrate in the applying step forms a thermally conductive member as a non-flowable cured product within about 120 minutes after application. The temperature for curing after application to the substrate is not particularly limited, and may be, for example, a temperature of 15°C or more and 60°C or less. In order to reduce thermal damage to the substrate, etc., the temperature may be 15°C or more and 40°C or less. Specifically, when the substrate is polycarbonate or PET with poor heat resistance, it is preferred not to heat the substrate. When the thermally conductive silicone composition is a heat-curable composition, the composition may be applied to the substrate, etc. and then heated, or may be cured using heat from a heat dissipation member. When the thermally conductive filler is aluminum hydroxide, the temperature in the case of thermal curing may be, for example, 40°C or more and 150°C or less, or when the thermally conductive filler is aluminum oxide, the temperature in the case of thermal curing may be 40°C or more and 180°C or less.
[0087] When a thermally conductive member is used as a gap filler, the substrate to which the gap filler is applied is not particularly limited, and examples thereof include resins (e.g., polyethylene terephthalate (PET), poly(1,4-butylene terephthalate) (PBT) and polycarbonate), ceramics, glass and metals (e.g., aluminum).
[0088] The thermally conductive member produced by the method has high flexibility and high heat dissipation performance. Since the thermally conductive member according to the present invention has flexibility corresponding to a penetration of 10 or more and 50 or less defined by JIS K 6249 and can fill fine gaps, the thermally conductive member has high adhesiveness and heat dissipation performance. In addition, even if an impact from the outside is applied to the thermally conductive member, damage and deformation of the heat dissipation member can be suppressed. The thermal conductivity of the heat-conducting member according to the present invention is not particularly limited, and is, for example, 2.0 W / m·K or more.
[0089] The present invention also provides a method for reducing the hardness of a cured product obtained by curing a thermally conductive silicone composition, the method comprising adding a component (C) to the thermally conductive silicone composition, wherein the component (C) is an organopolysiloxane containing a silanol group having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C., wherein the thermally conductive silicone composition comprises: a component (A) which is an organopolysiloxane containing an alkenyl group; a component (B) which is an organopolysiloxane having two or more hydrosilyl groups in one molecule; a component (D) which is an addition reaction catalyst; and a component (E) which is a thermally conductive filler of one or more types selected from the group consisting of metals, metal oxides, metal hydroxides, metal nitrides, and metal carbides, wherein the thermally conductive filler has a viscosity of 30 mPa·s or more and a viscosity of 50 mPa·s or less. 2 / g or less, and an average particle size of 1 μm to 100 μm; and component (F) which is a crosslinking agent.
[0090] Based on the total amount of component (A) and component (B) excluding component (D) as 100 parts by mass, the thermally conductive silicone composition according to the present invention may have the following chemical composition: 2 parts by mass or more and less than 90 parts by mass of component (A) which is an alkenyl group-containing organopolysiloxane; 10 parts by mass or more and less than 98 parts by mass of component (B) which is an organopolysiloxane having two or more hydrosilyl groups in one molecule; 3 parts by mass or more and 100 parts by mass or less of component (C) which is a silanol group-containing organopolysiloxane having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C.; Component (D) as an addition reaction catalyst; 500 parts by mass or more and 2,000 parts by mass or less of component (E) as a thermally conductive filler, which is one or more types of thermally conductive fillers selected from the group consisting of metals, metal oxides, metal hydroxides, metal nitrides, and metal carbides, the thermally conductive filler having a thermal conductivity of 30 m 2 / g or less, and an average particle size of 1 μm to 100 μm; and 1 part by mass or more and 10 parts by mass or less of component (F) which is a crosslinking agent, The component (D) is contained in an amount of 0.5 ppm or more and 1,000 ppm or less based on the total mass of the thermally conductive silicone composition. [Example]
[0091] The present invention will be specifically described based on the examples, but the present invention is not limited to the following examples. Tables 1 and 2 show the mixing ratios of the components in the examples and comparative examples, and the evaluation results. The numerical values of the mixing ratios shown in Tables 1 and 2 are expressed in parts by mass. The viscosity stated in the specification can be measured by a rotational viscometer (JIS K7117-2) at 25° C. and a shear rate of 10 / sec.
[0092] Method for producing a cured product (thermally conductive member) of a thermally conductive silicone composition: The first liquid and the second liquid described in each of the Examples and Comparative Examples were weighed at a ratio of 1:1, mixed thoroughly by a stirrer, and then degassed by a vacuum pump to produce each thermally conductive silicone composition. Each of these thermally conductive silicone compositions was cured at 23° C. for 24 hours to obtain a thermally conductive member, each of which was a cured product and a test piece for various evaluations.
[0093] Methods for measuring needle penetration: The first liquid and the second liquid described in each embodiment and comparative example were weighed at a ratio of 1:1, mixed thoroughly by a stirrer, and then degassed by a vacuum pump. The resultant was placed in a transparent cylindrical container and then cured at 23° C. for 24 hours to obtain a cylindrical cured product. According to the method of JIS K 6253 of The Society of Rubber Industry Japan standard, the penetration is measured using a penetration tester in an environment at 23°C. Specifically, the penetration tester is pressed from directly above the surface of the obtained cylindrical cured product, and penetration is performed for 5 seconds. Subsequently, the reading on the indicator is recorded as an integer. Three measurements are performed using a penetration tester, and the average value of the measurement results is used. In general, as the penetration becomes smaller, the flexibility becomes lower. Preferably, the penetration of the cured product of the thermally conductive silicone composition of the present invention is 10 or more and 50 or less. When the penetration exceeds 50, the strength of the cured product is insufficient. When the penetration is less than 10, it is believed that the flexibility of the cured product will be impaired, and when the thermally conductive silicone composition is placed in the gap between the heating element and the heat sink and vibrates after being cured in the gap, the fluidity is insufficient.
[0094] Method for measuring the specific gravity of the upper portion and the specific gravity of the lower portion and evaluating the sedimentation inhibition: In order to confirm the storage stability of the thermally conductive silicone composition, the precipitation inhibition was evaluated. When the evaluation result of the precipitation inhibition was favorable, the storage stability was determined to be favorable. The first liquid and the second liquid described in each of the Examples and Comparative Examples were each added in an amount of about 0.7 L to each container in which the inner package was placed in a 1 L metal cylindrical can. A polyethylene film having a thickness of 0.05 mm was placed on the upper portion thereof, and the container was closed with the lip of the metal can, and the container was left to stand at room temperature (23° C.) for 1,000 hours. After standing for 1,000 hours, the contents were taken out from the top to prevent the upper and lower parts from mixing, and were divided into three parts. The upper third of the contents is referred to as the upper part, and the lower third of the contents is referred to as the lower part. The first liquid and the second liquid in the upper part were weighed at a ratio of 1:1, mixed thoroughly by a stirrer, and then degassed by a vacuum pump, and the same operation was performed on the lower part. The resultant was poured into a plate-shaped die having a length of about 10 cm, a width of about 10 cm and a thickness of 2 mm, and cured at 23°C for 24 hours to obtain a cured product. The specific gravity (density) (g / cm 3 ). In the evaluation of precipitation inhibition, the one in which the specific gravity difference between the upper part and the lower part was less than 0.10 was determined as A, the one in which the specific gravity difference was 0.10 or more and less than 0.20 was determined as B, the one in which the specific gravity difference was 0.20 or more and less than 0.30 was determined as C, and the one in which the specific gravity difference was 0.30 or more was determined as D. The evaluation result is preferably B or better.
[0095] Methods for measuring thermal conductivity: The first liquid and the second liquid described in each embodiment and comparative example were weighed at a ratio of 1:1, fully mixed by a stirrer, and then degassed by a vacuum pump. The resulting thermally conductive silicone composition was poured into a columnar die having a diameter of 30 mm and a height of 6 mm, and then cured at 23°C for 24 hours to obtain each columnar cured product. The thermal conductivity of the cured product was measured by a measuring device (TPS-500 manufactured by Kyoto Electronics Manufacturing Co., Ltd.) based on the hot disc method according to ISO 22007-2. The sensor was placed between the two columnar cured products produced as described above, and the thermal conductivity was measured by a measuring device. The thermal conductivity is preferably 2.0 W / m·K or more.
[0096] Method for measuring adhesion: The first liquid and the second liquid described in each example and comparative example were discharged in an amount of 0.25 cc on a PET substrate using MPP-3 manufactured by Musashi Engineering, Inc. Then, the substrate was turned over and vibrated at 5 Hz for 30 seconds, and evaluation was performed. The evaluation result is determined as follows: The determined result is preferably B or better. A: When the substrate is turned over and vibrated, the liquid does not drip. B: When the substrate is turned over, the liquid does not drip, but when the substrate is vibrated, the liquid drips. C: Liquid drips when the substrate is turned over.
[0097] Method for measuring pump-out resistance: The first liquid and the second liquid described in each embodiment and comparative example were weighed at a ratio of 1:1 and mixed thoroughly by a stirrer. The mixture was applied to a 70 mm×70 mm aluminum substrate. Spacers with a thickness of 2 mm were placed at both ends of the aluminum substrate, and a 70 mm×70 mm PET substrate was placed on the aluminum substrate and pressed from above. The outline of the mixture pressed at this time was drawn with a pen, and the initial area was obtained. The sample was placed at 40°C for 20 minutes and vibrated 3,000 times at 10 Hz and 0.15 mm displacement. The area of the profile after vibration was obtained as the area after the test. The pump-out ratio of the area after the test to the initial area was evaluated as follows. A: 100% or more and less than 105% B: 105% or more and less than 110% C: 110% or more and less than 115% D: 115% or above
[0098] Method for testing heat resistance: The first liquid and the second liquid described in each embodiment and comparative example were weighed at a ratio of 1:1, fully mixed by a stirrer, and then degassed using a vacuum pump. The resultant was poured into a columnar die having a diameter of 30 mm and a height of 6 mm, and then cured at 23°C for 24 hours to obtain a columnar cured product. Each cured product was cooled at room temperature for 60 minutes and allowed to stand at 200°C for 24 hours for durability testing. In the specification, the condition of leaving the test piece at a temperature of 200°C for 24 hours is also referred to as high temperature exposure or high temperature durability test. The cured product after the durability test was left to stand at room temperature for 1 hour. The measurement was performed using a measuring device (TPS-500 manufactured by Kyoto Electronics Manufacturing Co., Ltd.) based on the hot plate method according to ISO 22007-2. A sensor was placed between the two columnar cured products produced as described above, and the thermal conductivity was measured by the measuring device. When the thermal conductivity after the durability test was 2.0 W / m·K or more, the cured product was evaluated to have desired heat resistance.
[0099] Methods for evaluating line breakage: The thermally conductive silicone composition was loaded into a dispenser (MPP3 manufactured by Musashi Engineering, Inc.), and the thermally conductive silicone composition was applied as beads having a width of 10 mm and a length of 20 mm from a height of 2.5 mm above the aluminum plate using the dispenser. The thermally conductive silicone composition was discharged at five locations at intervals of 10 mm, and four bead lengths were measured. When the average value of the bead lengths was close to 10 mm, the line breakage was judged to be good. When the average value was close to 0 mm, the line breakage was judged to be poor. The evaluation results are expressed in the following three stages including A (good), B (fair), and C (poor). A: 6mm or above B: 2mm or more and less than 6mm C: less than 2mm
[0100] Method for assessing the amount of low molecular weight cyclic siloxanes: The first liquid and the second liquid described in each embodiment and comparative example are weighed at a ratio of 1:1, fully mixed by a stirrer, and then degassed by a vacuum pump. The resulting product is poured into a plate-shaped die having a width of 100mm, a length of 100mm and a height of 6mm, and then cured at 23°C for 24 hours to obtain a cured product. The cured product weighed in an amount of 0.3g is placed in a 10mL acetone solution in a sample vial. The vial is closed and extraction is performed for more than 12 hours. Using this extraction solution, low molecular weight cyclic compounds ((D4) to (D8)) are weighed by gas chromatography.
[0101] Method for producing a cured product of a thermally conductive silicone composition: (Example 1) According to the chemical composition shown in the column of Example 1 in the table, each of the first liquid and the second liquid was produced by the following process. The unit of the mixing ratio of each component shown in the table is part by mass.
[0102] [First Liquid of Examples 1 to 3] The diorganopolysiloxane having an alkenyl group as component (A), the polydimethylsiloxane containing a silanol group as component (C), the platinum-divinyltetramethyldisiloxane complex as component (D), and a half amount of the silane coupling agent "SILANE 25013VP" (manufactured by Wacker Chemie AG) as an optional component were weighed and added together, and kneaded at room temperature for 30 minutes using a planetary mixer. Component (A) is a linear dimethyl polysiloxane having alkenyl groups only at both ends, and its viscosity is 150 mPa·s. Component (C) is a linear dimethyl polysiloxane having one silanol group at each of both ends and having a viscosity of 50 mPa·s. Thereafter, half the amount of spherical alumina (component (E-1)) having an average particle size of 45 μm and amorphous alumina (component (E-2)) having an average particle size of 3 μm (these two components are thermally conductive fillers used as component (E)) were added, and the mixture was kneaded at room temperature for 15 minutes using a planetary mixer. Thereafter, half the amount of the silane coupling agent, half the amount of each of the spherical thermally conductive filler and the amorphous thermally conductive filler as the component (E) were added and kneaded at room temperature for 15 minutes using a planetary mixer, thereby preparing a first liquid. Spherical alumina DAM-45 (average particle size: 45 μm, BET specific surface area: 0.15 m 2 / g) as spherical alumina (E-1). Fine-grained alumina SA34 (average particle size: 3 μm, BET specific surface area: 1.9 m 2 / g) as amorphous alumina (E-2).
[0103] [Second liquid of Examples 1 to 3] The diorganopolysiloxane having the same alkenyl group as the first liquid as component (A), the linear diorganopolysiloxane having a viscosity of 70 mPa·s and two hydrogen atoms at both ends as component (B), the crosslinking agent as component (F), and the silane coupling agent "SILANE 25013VP" manufactured by Wacker Chemie AG as an optional component were weighed separately and added together, and kneaded at room temperature for 30 minutes using a planetary mixer. The crosslinking agent as component (F) was dimethylpolysiloxane having 12 hydrogen atoms bonded to silicon atoms in the side chain, a hydrogen content of 0.17% by weight, and a viscosity of 70 mPa·s. Then, half the amount of the silane coupling agent, and the same spherical thermally conductive filler (E-1) and amorphous thermally conductive filler (E-2) as the first liquid as component (E) were added, and kneaded at room temperature for 15 minutes using a planetary mixer to prepare a second liquid.
[0104] [Example 4] The first liquid and the second liquid were prepared in the same manner as in Example 2, except that aluminum hydroxide SBX73 manufactured by Nippon Light Metal Co., Ltd. was used instead of the amorphous aluminum oxide. As aluminum hydroxide (E-3), amorphous aluminum hydroxide SBX73 (average particle size: 10 μm, BET specific surface area: 1.5 m) manufactured by Nippon Light Metal Co., Ltd. was used. 2 / g).
[0105] [Example 5] The first liquid and the second liquid were prepared in the same manner as in Example 2 except that a linear dimethylpolysiloxane having no silanol groups at both ends and in the side chain, a viscosity of 50 mPa·s and one trimethoxysilyl group at each of both ends was used as component (C).
[0106] [Example 6] The first liquid and the second liquid were prepared in the same manner as in Example 2, except that amorphous silica AEROSIL 200 (E-4) manufactured by EVONIK Japan Co., Ltd. was added thereto after kneading amorphous alumina as component (E) and kneading was performed for 15 minutes. Silica AEROSIL 200 (average particle size: 20 nm, BET specific surface area: 200 m 2 / g) as silicon dioxide (E-4).
[0107] [Example 7] The first liquid and the second liquid were prepared in the same manner as in Example 2, except that a linear dimethylpolysiloxane having only one alkenyl group at each of both ends and having a viscosity of 1,000 mPa·s was used as component (A).
[0108] [Example 8] The first liquid and the second liquid were prepared in the same manner as in Example 2, except that polymethylphenylsiloxane having one silanol group at each of both ends and having a viscosity of 150 mPa·s was used as component (C).
[0109] [Comparative Example 1] The first liquid and the second liquid were prepared in the same manner as in Example 1, except that the component (C) was not added thereto.
[0110] [Comparative Example 2] The first liquid and the second liquid were prepared in the same manner as in Example 1, except that the content of the component (C) was reduced to 1 part by mass.
[0111] [Comparative Example 3] The first liquid and the second liquid were prepared in the same manner as in Example 1, except that the content of the component (C) was increased to 150 parts by mass.
[0112] [Comparative Example 4] The first liquid and the second liquid were prepared in the same manner as in Example 1 except that 100 parts by mass of a linear dimethylpolysiloxane having no silanol groups at both ends and in the side chain, a viscosity of 50 mPa·s, and trimethoxy groups at both ends, which was the same compound as used as component (C) in Example 5, was added.
[0113] [Comparative Example 5] The first liquid and the second liquid were prepared in the same manner as in Example 2 except that 50 parts by mass of dimethylpolysiloxane having silanol groups at both ends and having a viscosity of 700 mPa·s was added as component (C).
[0114] [Comparative Example 6] The first liquid and the second liquid were prepared in the same manner as in Example 2, except that after the spherical alumina (E-1) and the amorphous alumina (E-2) as the component (E) were kneaded, 5 parts by mass of AEROSIL200 manufactured by EVONIK Japan Co., Ltd. were added thereto and kneaded for 15 minutes.
[0115] [Comparative Example 7] The first liquid and the second liquid were prepared in the same manner as in Comparative Example 1, except that starch manufactured by FUJIFILM Wako Chemical Corporation was added as component (G) after kneading spherical alumina (E-1) and amorphous alumina (E-2) as component (E) and kneading was performed for 15 minutes.
[0116] [Comparative Example 8] The first liquid and the second liquid were prepared in the same manner as in Example 2 except that an organopolysiloxane (viscosity: 150 mPa·s) having one silanol group at each of both ends and an alkenyl group in a side chain was used as component (A) and component (C) was not added.
[0117] [Comparative Example 9] The first liquid and the second liquid were prepared in the same manner as in Example 2, except that only the organopolysiloxane containing no silanol group (which was the same as the organopolysiloxane used in Example 5) was used as component (C), and the same silica as used in Example 6 was added thereto as component (E).
[0118] [Comparative Example 10] The first liquid and the second liquid were prepared in the same manner as in Example 1 except that component (C) was not added and the addition amounts of spherical alumina (E-1) and amorphous alumina (E-2) of component (E) were 250 parts by mass and 200 parts by mass, respectively.
[0119] The evaluation results are shown in Tables 1 and 2. In Examples 1 to 3, 5 to 100 parts by mass of an organopolysiloxane having a silanol group as component (C) was mixed, but the needle penetration fell within the range of 10 to 50, and the result of the anti-pumping property was good. Therefore, it was confirmed that the cured product had sufficient flexibility and favorable anti-pumping property after curing. The thermal conductivity was 2.0 W / m·K or more, and the thermal conductivity was favorable. After standing for 1,000 hours, the specific gravity difference between the upper and lower parts was less than 1, and therefore the precipitation inhibition was also favorable. For line breakage, 6 mm or more was reached, and the line breakage was good. The amount of low molecular weight cyclic compounds was 500 ppm or less, and therefore favorable results were obtained.
[0120] In the chemical composition of Example 4, aluminum hydroxide is used instead of amorphous aluminum oxide. The thermal conductivity is lower than that of Examples 1 to 3, but the precipitation inhibition is more improved than that of Example 2, in which the chemical composition is the same as that of Example 4 except that aluminum hydroxide is included. Due to the addition of aluminum hydroxide, the thermal conductivity decreases after the high temperature durability test. This decrease is due to the dehydration and decomposition of aluminum hydroxide during exposure to high temperature. Therefore, the heat resistance is lower than that of Example 2, but it is also within an acceptable range. The needle penetration is in the range of 10 to 50, which indicates favorable flexibility.
[0121] In the chemical composition of Example 5, dimethyl polysiloxane containing no silanol group was added as component (C). The flexibility and storage stability were favorable, but the pump-out resistance and line breakage were lower than those of Example 3, in which the total amount of component (C) was the same as that of Example 5. When the organopolysiloxane containing no silanol group was mixed, the amount of the organopolysiloxane containing no silanol group to be mixed was made equal to or less than the amount of the organopolysiloxane having a silanol group. Therefore, it was confirmed that a thermally conductive silicone composition having pump-out resistance of B or better and line breakage of B or better was obtained.
[0122] In the chemical composition of Example 6, an organopolysiloxane having a silanol group as component (C) and silica as component (E) were added. The precipitation inhibition was the same as in Example 2, wherein the total amount of component (C) in Example 2 was the same as in Example 6. The needle penetration was reduced due to the addition of silica. The adhesion was lower than that of Example 2.
[0123] In the chemical composition of Example 7, a diorganopolysiloxane having alkenyl groups at both ends and having a viscosity of 1,000 mPa·s was used as component (A). Compared with Example 2 in which the chemical composition other than component (A) was the same as that of Example 7, precipitation inhibition was improved, but flexibility was slightly reduced and needle penetration was reduced.
[0124] In the chemical composition of Example 8, dimethylphenyl polysiloxane having silanol groups at both ends and a viscosity of 150 mPa·s was used as component (C). The needle penetration was lower than that of Example 2, in which the total amount of component (C) was the same as that of Example 8.
[0125] In the chemical composition of Comparative Example 1, component (C) was not added. Therefore, the flexibility and the effect of suppressing precipitation were reduced, and the results of needle penetration, anti-pumping property, and wire breakage were reduced. In the chemical composition of Comparative Example 2, the amount of component (C) was reduced to 1 part by mass. Due to the reduction in the amount of component (C), precipitation inhibition, anti-pumping property, and line breakage property were deteriorated.
[0126] In the chemical composition of Comparative Example 4, only dimethyl polysiloxane without a silanol group was used as component (C). The flexibility was high, and the needle penetration was improved to 40. However, the anti-pumping property, the effect of inhibiting precipitation, and the line breakage were significantly lower than those of Example 3, in which the total amount of component (C) was the same as that of Comparative Example 4. This indicates that when only an organopolysiloxane without a silanol group was used, the above three properties could not be maintained.
[0127] In the chemical composition of Comparative Example 5, a diorganopolysiloxane having silanol groups at both ends and having a viscosity of 700 mPa·s was used as component (C). The precipitation inhibition and anti-pumping properties were lower than those of Example 2, in which the total amount of component (C) was the same as that of Comparative Example 5. It is considered that due to the use of a diorganopolysiloxane having silanol groups at both ends and having an elongated molecular chain, the density of hydrogen bonds was low, and the precipitation inhibition effect and the anti-pumping property effect were reduced.
[0128] In the chemical composition of Comparative Example 6, component (C) was added, and 5 parts by mass of silica was added as component (E). Due to silica, precipitation suppression was favorable. However, the amount of silica mixed was large, adhesion was deteriorated, and penetration was reduced.
[0129] In the chemical composition of Comparative Example 7, starch was added as component (G). The needle penetration, precipitation inhibition, adhesion, pump-out resistance, and line breakage were all within acceptable ranges, and the results were favorable. The thermal conductivity before exposure to high temperature was 2.0 W / m·K or more, which was favorable. Due to the decomposition of starch, the thermal conductivity after exposure to high temperature decreased to less than 2.0 W / m·K.
[0130] In the chemical composition of Comparative Example 8, an organopolysiloxane having silanol groups at both ends and an alkenyl group in a side chain was used as component (A), and component (C) was not added. Precipitation inhibition, thermal conductivity, adhesion, pump-out resistance, and line breakage were all within acceptable ranges, and the results were favorable. Due to the absence of component (C), needle penetration decreased.
[0131] In the chemical composition of Comparative Example 9, only the organopolysiloxane containing no silanol group was used as component (C), and silica was added as component (E). The precipitation inhibition, thermal conductivity, pump-out resistance, and line breakage were all within acceptable ranges, but the needle penetration and adhesion were deteriorated due to the addition of silica.
[0132] In the chemical composition of Comparative Example 10, the amount of thermally conductive filler as component (E) was reduced compared to Example 1. Since the amount of thermally conductive filler was reduced, precipitation inhibition fell within an acceptable range. However, thermal conductivity was 2.0 W / m·K or less, and line breakage was rated as C.
[0133] In all of Examples 1 to 9, the total content of low molecular weight cyclic siloxanes (D4) to (D8) was 500 ppm or less. In all cases, the flash point of the thermally conductive silicone composition was 100° C. or more. Since the content of the low molecular weight cyclic siloxane is small, the amount of low molecular weight cyclic siloxane volatilized during overheating (for example, during heating to 100° C. or more for 1 minute or more) is small, and thus contact failure is less likely to occur in electronic components and the like.
[0134] [Table 1]
[0135] [Table 2]
[0136] Some or all of the above embodiments may be described in the following appendix, but are not limited to the following description.
[0137] (Appendix 1) A thermally conductive silicone composition comprising: Component (A) which is an alkenyl group-containing organopolysiloxane; Component (B) which is an organopolysiloxane having two or more hydrosilyl groups in one molecule; Component (C) which is a silanol group-containing organopolysiloxane having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C.; a component (D) which is an addition reaction catalyst; Component (E), which is one or more thermally conductive fillers selected from the following group: metals, metal oxides, metal hydroxides, metal nitrides, and metal carbides, the thermally conductive filler having 30m 2 / g or less, and an average particle size of 1 μm to 100 μm; and Component (F), which is a crosslinking agent, wherein The component (C) is contained in an amount of 3 parts by mass or more based on 100 parts by mass of the total amount of the component (A) and the component (B), Based on 100 parts by weight of the total amount of component (A) and component (B), the BET specific surface area of the composition is 50 m 2 / g or more of the filler is 3 parts by mass or less.
[0138] (Appendix 2) The thermally conductive silicone composition as described in Appendix 1, wherein component (C) is a linear organopolysiloxane having neither an alkenyl group nor a hydrosilyl group and having at least one silanol group at both ends of the molecular chain.
[0139] (Appendix 3) The thermally conductive silicone composition as described in Appendix 1 or 2, wherein the content of the silanol group in component (C) is 1 mass % or more and 10 mass % or less.
[0140] (Appendix 4) The thermally conductive silicone composition as described in any one of Appendices 1 to 3, wherein the content of component (C) is 5 parts by mass or more and 100 parts by mass or less, based on 100 parts by mass of the total amount of component (A) and component (B).
[0141] (Appendix 5) The thermally conductive silicone composition as described in any one of Appendices 1 to 4, wherein the content of component (E) is 500 parts by mass or more and 2,000 parts by mass or less, based on 100 parts by mass of the total amount of component (A) and component (B).
[0142] (Appendix 6) The thermally conductive silicone composition as described in any one of Appendices 1 to 5, wherein component (E) is at least one selected from the following group: aluminum oxide, aluminum hydroxide, magnesium oxide, magnesium hydroxide, zinc oxide, aluminum nitride, and boron nitride.
[0143] (Appendix 7) A thermally conductive silicone composition as described in any one of Appendices 1 to 6, wherein component (F) has at least one hydrogen atom (hydrogen silyl group) bonded to a silicon atom in a side chain, and the number of the hydrosilyl groups in one molecule of component (F) is 3 or more.
[0144] (Appendix 8) The thermally conductive silicone composition as described in any one of Appendices 1 to 7, wherein the thermally conductive silicone composition forms a cured product after curing, the cured product having a needle penetration of 10 or more and 50 or less according to JIS K6249.
[0145] (Appendix 9) A thermally conductive silicone composition as described in any one of Appendices 1 to 8, wherein the thermally conductive silicone composition forms a cured product after curing, and the cured product has a thermal conductivity of 2.0 W / m·K or more after curing.
[0146] (Appendix 10) A thermally conductive silicone composition as described in any one of Appendices 1 to 9, wherein the content of each of octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), dodecamethylcyclohexasiloxane (D6), tetradecamethylcycloheptasiloxane (D7), and hexadecamethylcyclooctasiloxane (D8) is less than 0.1 parts by mass, based on 100 parts by mass of the total amount of component (A) and component (B).
[0147] (Appendix 11) A method for producing a thermally conductive silicone composition as described in Appendix 1, comprising: In a first step, component (A) an alkenyl-containing organopolysiloxane, component (C) an organopolysiloxane containing a silanol group having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C., component (E) a thermally conductive filler, and component (D) an addition reaction catalyst are mixed to obtain a first liquid; and In the second step, component (A) an alkenyl-containing organopolysiloxane, component (B) an organopolysiloxane having two or more hydrosilyl groups in one molecule, component (C) an organopolysiloxane containing a silanol group having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C., component (E) a thermally conductive filler, and component (F) a cross-linking agent are mixed to obtain a second liquid, thereby producing a two-component thermally conductive silicone composition.
[0148] (Appendix 12) A method for producing a thermally conductive component, comprising: a mixing step of mixing a first liquid and a second liquid of the two-component thermally conductive silicone composition as described in Appendix 11 to obtain a mixture; an applying step of applying the mixture of the first liquid and the second liquid obtained in the mixing step to the substrate; and The curing step is to cure the uncured mixture applied in the applying step.
[0149] (Appendix 13) A method for producing a thermally conductive member as described in Appendix 12, wherein the thermally conductive member is used as a gap filler.
[0150] (Appendix 14) A method for reducing the hardness of a cured product, wherein the cured product is obtained by curing a thermally conductive silicone composition, the method comprising: A component (C) is added to the thermal conductive silicone composition, wherein the component (C) is an organopolysiloxane containing a silanol group and having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C. The thermal conductive silicone composition comprises Component (A) which is an alkenyl group-containing organopolysiloxane; Component (B) which is an organopolysiloxane having two or more hydrosilyl groups in one molecule; a component (D) which is an addition reaction catalyst; Component (E), which is one or more types of thermally conductive fillers selected from the following group: metals, metal oxides, metal hydroxides, metal nitrides, and metal carbides, the thermally conductive filler having 30m 2 / g or less, and an average particle size of 1 μm to 100 μm; and Component (F) which is a cross-linking agent.
[0151] (Appendix 15) The thermally conductive silicone composition as described in Appendix 1 comprises: 2 parts by mass or more and less than 90 parts by mass of component (A), based on 100 parts by mass of the total amount of component (A) and component (B); 10 parts by mass or more and less than 98 parts by mass of component (B), based on 100 parts by mass of the total amount of component (A) and component (B); 3 parts by mass or more and 100 parts by mass or less of component (C), based on 100 parts by mass of the total amount of component (A) and component (B); 0.5 ppm or more and 1,000 ppm or less of component (D), based on the total mass of the thermally conductive silicone composition; 500 parts by mass or more and 2,000 parts by mass or less of component (E), based on 100 parts by mass of the total amount of component (A) and component (B); and 1 part by mass or more and 10 parts by mass or less of component (F) based on 100 parts by mass of the total amount of component (A) and component (B).
Claims
1. A thermally conductive silicone composition comprising: Component (A) which is an alkenyl group-containing organopolysiloxane; Component (B) which is an organopolysiloxane having two or more hydrosilyl groups in one molecule; Component (C) which is a silanol group-containing organopolysiloxane having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C.; a component (D) which is an addition reaction catalyst; Component (E), which is at least one or more types of thermally conductive fillers selected from the following group: metals, metal oxides, metal hydroxides, metal nitrides, and metal carbides, the thermally conductive filler having 30m 2 / g or less, and an average particle size of 1 μm to 100 μm; and Component (F), which is a crosslinking agent, wherein Based on 100 parts by mass of the total amount of the component (A) and the component (B), the content of the component (C) is 3 parts by mass or more, Based on 100 parts by weight of the total amount of the component (A) and the component (B), the BET specific surface area of the composition is 50 m 2 / g or more of the filler is 3 parts by mass or less.
2. The thermally conductive silicone composition according to claim 1, wherein the component (C) is a linear organopolysiloxane having neither an alkenyl group nor a hydrosilyl group and having at least one silanol group at both ends of the molecular chain.
3. The thermally conductive silicone composition according to claim 1 or 2, wherein the content of the silanol groups in the component (C) is 1 mass % or more and 10 mass % or less.
4. The thermally conductive silicone composition according to claim 1 or 2, wherein the content of component (C) is 5 parts by mass or more and 100 parts by mass or less, based on 100 parts by mass of the total amount of component (A) and component (B).
5. The thermally conductive silicone composition according to claim 1 or 2, wherein the content of component (E) is 500 parts by mass or more and 2,000 parts by mass or less, based on 100 parts by mass of the total amount of component (A) and component (B).
6. The thermally conductive silicone composition according to claim 1 or 2, wherein the component (E) is at least one selected from the group consisting of aluminum oxide, aluminum hydroxide, magnesium oxide, magnesium hydroxide, zinc oxide, aluminum nitride, and boron nitride.
7. The thermally conductive silicone composition according to claim 1 or 2, wherein the component (F) has at least one hydrogen atom (hydrosilyl group) bonded to a silicon atom in a side chain, and the number of the hydrosilyl groups in one molecule of the component (F) is 3 or more. 8 . The thermally conductive silicone composition according to claim 1 , wherein the thermally conductive silicone composition forms a cured product after curing, the cured product having a needle penetration of 10 or more and 50 or less according to JIS K6249. 9 . The thermally conductive silicone composition as claimed in claim 1 , wherein the thermally conductive silicone composition forms a cured product after being cured, and the cured product has a thermal conductivity of 2.0 W / m·K or more after being cured.
10. The thermally conductive silicone composition according to claim 1 or 2, wherein the total content of octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), dodecamethylcyclohexasiloxane (D6), tetradecamethylcycloheptasiloxane (D7) and hexadecamethylcyclooctasiloxane (D8) is less than 0.1 parts by mass, based on 100 parts by mass of the total amount of the component (A) and the component (B).
11. A method for producing the thermally conductive silicone composition according to claim 1, comprising: In a first step, component (A) an alkenyl-containing organopolysiloxane, component (C) an organopolysiloxane containing a silanol group having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C., component (E) a thermally conductive filler, and component (D) an addition reaction catalyst are mixed to obtain a first liquid; and In the second step, component (A) an alkenyl-containing organopolysiloxane, component (B) an organopolysiloxane having two or more hydrosilyl groups in one molecule, component (C) an organopolysiloxane containing a silanol group having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C., component (E) a thermally conductive filler, and component (F) a crosslinking agent are mixed to obtain a second liquid, thereby producing a two-component thermally conductive silicone composition.
12. A method for producing a thermally conductive component, comprising: A mixing step of mixing the first liquid and the second liquid of the two-component thermally conductive silicone composition as claimed in claim 11 to obtain a mixture; an applying step of applying the mixture of the first liquid and the second liquid obtained in the mixing step to a substrate; as well as A curing step of curing the uncured mixture applied in the applying step. 13 . The method for producing a thermally conductive member according to claim 12 , wherein the thermally conductive member is used as a gap filler.
14. A method for reducing the hardness of a cured product obtained by curing a thermally conductive silicone composition, the method comprising: Adding a component (C) to the thermally conductive silicone composition, the component (C) being an organopolysiloxane containing a silanol group having a viscosity of 10 mPa·s or more and 500 mPa·s or less at 25° C., The thermally conductive silicone composition comprises Component (A) which is an alkenyl group-containing organopolysiloxane; Component (B) which is an organopolysiloxane having two or more hydrosilyl groups in one molecule; a component (D) which is an addition reaction catalyst; Component (E), which is one or more types of thermally conductive fillers selected from the following group: Metal, metal oxide, metal hydroxide, metal nitride and metal carbide, the thermal conductive filler has 30m 2 / g or less, and an average particle size of 1 μm to 100 μm; and Component (F) which is a cross-linking agent.
Citation Information
Patent Citations
Heat conductive silicone composition and cured product of the same
JP2011089079A
Silicone composition
WO2016103424A1